Development model of public open space in Bandar Lampung city’s regional government - Fritz Akhmad Nuzir, Ida Farida, Agus Purnomo, (Opción, 2019)
The aim of the study is to investigate development model of public open space in Bandar Lampung city’s regional government. The method used in this developmental research is qualitative - descriptive approach. The preliminary findings in this study are the number of lands in Bandar Lampung city that has not been utilized optimally. In conclusion, there are only three most ideal public open spaces, namely: Pahoman stadium (in the city centre); Kalpataru Field (in the western city boundary); and Baruna Field at Panjang (in the southeastern city boundary).